THE INFLUENCE OF THE SOCIODRAMA-BASED PROJECT BASED LEARNING MODEL ON JAVANESE LANGUAGE LEARNING IN GRADE V STUDENTS OF SD NEGERI SAMBIREJO SURAKARTA FOR THE 2022/2023 ACADEMIC YEAR - Fadzilah Nurlaili; Oktiana Handini; Elinda Rizkasari (Universitas Muhammadiyah Muara Bungo, 2023)
This research is a quantitative research with the method used is the pre-experimental design method and using the one group pretest-posttest research design. The subjects in this study were students of class V, totaling 28 students. The data analysis technique used is the normality test with the one-sample Kolmogorov-Smirnov formula, Paired Sample t-tets. Based on data analysis on the effect of using sociodrama-based Project Based Learning on Javanese language learning, the average pretest result was 54.46, after being given the sociodrama-based Project Based Learning treatment the posttest results obtained an average of 78.04. Based on the paired sample t-test table, the t_count value is 30.797, this t_count value can be compared with t_table with dk = (N-1) so (28-1) = 27 at a 5% significance level, namely 2.056. Which means H_0 is rejected and H_a is accepted. So the hypothesis states that